Outcome of Lower Uterine Compressive Suture for the Management of Postpartum Hemorrhage Due to Placenta Previa During Cesarean Section - Sarker, Suravi; Das, Mrinal Kanti; Hoque, Al Mirajun; Sarkar, Sunandita; Sultana, Sharmin; Jesmin, Shahela; Khatun, Rokeya (TAJ: Journal of Teachers Association, 2023)
Background: Lower uterine compression suture (Cervical-Isthmic apposition suture technique) is a new but effective method to arrest postpartum hemorrhage (PPH). The effectiveness of the suture is not only due to local compression of the anterior and posterior walls of the uterus but also related to the indirect compression of the intramyometrial vessels running from the lateral edge of the lower uterine segment to its media part. Objectives: The aim of this study was to determine the outcome of uterine compression sutures for the management of PPH due to placenta previa during cesarean section. Materials and Methods: This hospital-based prospective observational study was conducted in the Department of Obstetrics and Gynecology of Rajshahi Medical College Hospital from January 2016 to December 2017. A total of 45 women who developed severe postpartum hemorrhage due to placenta previa during cesarean section were selected peroperatively or postoperatively as the study case. A lower uterine compression suture was given to all the patients. If the bleeding was not well controlled, then other adjunctive procedures were performed. Patients with a bleeding disorder, type I placenta previa, cases other than placenta previa, and morbid adherents of placenta were excluded from the study. The patients were examined postoperatively and again in 2nd week and 6th week after hospital discharge for evaluation of any complications. Data regarding history, physical findings, and investigation were collected from the patient and the patient's record. Result: Among the total of 45 cases, PPH was controlled in 88.9%(40) cases with compression sutures in the lower uterine segment, and only 11.1% (5) cases required additional procedures. It was observed that higher age groups, multiparous women, patients with <37 weeks of pregnancy, and previous history of cesarean section were significantly associated with a higher amount of bleeding. Conclusion: Lower uterine compressive compression suture is an effective and safe method to control PPH due to placenta previa during cesarean section and can preserve the uterus for further pregnancy and menstruation. TAJ 2022; 35: No-2: 35-41